Synthesis, characterization and electrochemical investigations of mixed-ligand copper(II)-organic supramolecular frameworks - Singh, Sandeep K.; Srivastava, Ashish Kumar; Srivastava, Krishna; Banerjee, Rahul; Prasad, Jagdish (Journal of Molecular Structure, 2017)
Two mixed-ligand copper(II)-organic coordination compounds with 5,5'-dimethyl-2,2'-bipyridine (5,5'-Me(2)bpy) as a primary ligand while aliphatic malonate (Hmal) and aromatic 2-hydroxynicotinate (2-OHNA) as secondary ligands, were synthesized. These complexes are formulated as: [Cu(Hmal)(5,5'-Me(2)bPY)(H2O)](ClO4) 1 and [Cu-2(2-OHNA)(2)(5,5'-Me(2)bpy)(2)(NO3)KNO3) 2. These two complexes were structurally characterized by single crystal X-ray diffraction analysis. Characterization was further supported by powder X-ray diffraction analysis, elemental analyses, FT-IR, FAB-MASS and TGA, DSC studies. Cyclic voltammetric and UV-visible spectral studies of these two complexes have also been done. The electrochemical studies of complex 1 in DMSO and DMF have shown that this complex undergoes quasi reversible diffusion-controlled one-electron transfer reaction without any chemical complication while complex 2 in DMSO undergoes quasi-reversible diffusion-controlled one electron transfer reaction, following EC mechanism. The electrochemical behaviour of complex 2 in DMF is complicated probably due to presence of more than one species in solution phase. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: 2 '-bipyridine; 3; 5; 5 '-dimethyl-2; 5-Tricarboxylic acid; Benzene-1; classification; Co-ordination-Compounds; Crystal-structures; cyclic voltammetry; magnetic properties; metal organic framework; Mixed-ligand complex; pi-pi stacking interaction; Polymers; Secondery Building Unit; Structural data; Supramolecular framework; Ternare Komplexe; X-ray diffraction

Syntheses and single crystal X-ray diffraction analysis of five isostructural 2D MOCCs - Singh, Sandeep K.; Srivastava, Krishna; Banerjee, Rahul; Prasad, Jagdish (Polyhedron, 2018)
Five two-dimensional metal-organic coordination compounds (MOCCs) have been solvothermally synthesized by the combination of 2-aminonicotinic acid (ANA) and transition metal ions, viz. Co(II), Ni (II), Cu(Il), Zn(II) and Cd(II), in water-ethanol mixed solvent. They are formulated as [CoC6H5N2O2)(2)], (Co-ANA); [Ni(C6H5N2O2)(2)], (Ni-ANA) [Cu(C6H5N2O2)(2)], (Cu-ANA), [Zn(C6H5N2O2)(2)], (Zn-ANA) and [Cd(C6H5N2O2)(2)], (Cd-ANA). Single crystal X-ray diffraction studies for the complexes Co-ANA, Ni-ANA and Cd-ANA have also been carried out. These three complexes crystallize in the tetragonal crystal system with the space group P4(1)2(1)2. The metal ions in all these complexes have an octahedral coordination environment. The six coordinations are satisfied by two pyridine N-atoms from two different ANA ligands and four oxygen atoms from two chelating carboxylate groups of another two ANA ligands. The topological motif of the coordination network is defined as 2-periodic net or square lattice (sql). These complexes were further characterized by elemental, FT-IR spectral, thermal and powder X-ray diffraction analyses. (C) 2018 Elsevier Ltd. All rights reserved.